Postprandial lipemic response in dairy-avoiding females following an equal volume of sheep milk relative to cow milk: A randomized controlled trial - Teng, Fei; Samuelsson, Linda M.; Milan, Amber Marie; Subbaraj, Arvind; Agnew, Michael; Shrestha, Aahana; Cameron-Smith, David; Day, Li (Frontiers in Nutrition, 2023)
Background: Sheep milk (SM) is an alternate dairy source, which despite many similarities, has both compositional and structural differences in lipids compared to cow milk (CM). Studies are yet to examine the apparent digestibility of SM lipids, relative to CM, and the potential impact on the plasma lipidome. Objective: To determine the response of the circulatory lipidome to equal volume servings of SM and CM, in females who avoid dairy products. Method: In a double-blinded, randomized, cross-over trial, self-described dairy avoiding females (n=30; 24.4±1.1 years) drank SM or CM (650 mL; 33.4 vs. 21.3 g total lipid content; reconstituted from spray dried milk powders) following an overnight fast. Blood samples were collected at fasting and at regular intervals over 4 h after milk consumption. The plasma lipidome was analyzed by LC-MS and fatty acids were quantified by GC-FID. Results: The overall postprandial triglyceride (TG) response was similar between SM and CM. TG concentrations were comparable at fasting for both groups, however they were higher after CM consumption at 30 minutes (interaction milk × time p=0.003), well before any postprandial lipemic response. This was despite greater quantities provided by SM. However, there were notable differences in the postprandial fatty acid response, with SM leading to an increase in short- and medium-chain fatty acids (MUFAs)(C6:0, C8:0, C10:0) and several long-chain fatty acids (LCFAs) (C18:1 t11, c9,t11-CLA and C20:0; interaction time × milk p<0.05). This corresponded to a greater postprandial response for medium chain triglycerides (MCTs) C10:0, including TG(10:0/14:0/18:1),TG(16:0/10:0/12:0) and TG(16:0/10:0/14:0) (interaction time × milk p<0.05). Conclusions: Despite a higher fat content, SM ingestion resulted in a greater circulating abundance of MCTs, without increasing total postprandial triglyceride response, when compared to CM. The greater abundance and postprandial appearance of MCTs may provide advantageous metabolic responses in children and adults.